Policy and Effectiveness of Distribution Channels on Product Sales - Fachrizal Yusha Akbar; Kusdi Raharjo; Saparila Worokinasih (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In today’s increasingly complex and fiercely competitive industrial world, logistics is said to be able to provide greater value to companies. Logistics activities are seen as an extension of production activities, which are a solution for companies to reap more profits. The purpose of this study is to determine the factors that influence the decline in turnover in the mid-mile enterprise fulfillment division based on the business model canvas and to determine how the internal control system works in the mid-mile enterprise fulfillment division. This study uses a qualitative descriptive approach to describe a company’s business model based on business model canvas theory and analyze internal control. In this study, data collection techniques include interviews, observations, documentation, and triangulation. The interview results will be processed using data triangulation techniques in accordance with the nine elements of the business model canvas. The results of the study indicate that the determination of shipping prices, which should be calculated based on shipping distance and tonnage, will affect the decline in turnover in the mid-mile enterprise fulfillment division. The nine elements of the business model canvas are examined to identify factors contributing to the decline in turnover.